Field screening of rice (Oryza sativa L.) genotypes for resistance to bacterial leaf blight (Xanthomonas oryzae pv. oryzae) disease - Acharya, Basistha; KC, Sujata (Journal of Agriculture and Natural Resources, 2021)
Rice is the most important crop in Nepal followed by maize and wheat in terms of area (1.4 million ha), production (5.15 million) and productivity (3.5 mt/ha). Bacterial leaf blight (BLB), caused by Xanthomonas oryzae pv. oryzae is considered to be the most widespread and destructive disease of rice in both irrigated and rainfed environments in Nepal. Use of host plant resistance is the most feasible and economical way to combat this disease. However, breakdown of resistance of a variety often occurs after few years of release due to genetic adaptation of the pathogen. Regular screening of the genotypes is utmost for developing the resistant genotypes. Considering the point, this investigation effort has been made to screen the rice genotypes against BLB under natural field condition at Khajura, Banke during 2018 and 2019. In the study, plants were assessed by measuring disease severity (percentage of leaf diseased) and area under the disease progress curve (AUDPC). Differences in resistance among the rice genotypes were observed in both of the tested year. Among the screened 150 rice genotypes during 2018, 6 genotypes scored resistant (R), 81 moderately resistant (MR), 59 moderately susceptible (MS) and 4 susceptible (S) to BLB. Whereas, in 2019, among the tested 315 rice genotypes, none of the genotypes were resistant, 183 MR, 131 MS and 1 S to BLB disease. This showed that the tested genotypes were composed of different genetic background.